Vision in Administrative Dimensions and Academic Administration of Teachers Naluang School Bangkok: Vision in Administrative Dimensions and Academic Administration of Teachers Naluang School Bangkok - Rianwilairat, Wichan; Rachatasirakul, Thanakrit; Krutkrongphan, Sirikawin (RATANABUTH JOURNAL, 2023)
This research aims to study 1) The level of vision in the management dimension 2) The level of academic administration 3) The relationship of the vision in the administrative dimension and the academic administration of the teachers of Naluang School Bangkok. This population was 54 teachers of Naluang School Bangkok. The instrument used was a questionnaire. data analysis Finding Percentage, Mean, and Standard Deviation and find a relationship by Pearson’s Product Moment Correlation Coefficient. The results of the research found that most of the respondents were female, 93 people aged 30-40 years, 104 people, 36 people with bachelor’s degree, 120 people with less than 10 years of work experience, representing 153 people 1) Vision in overall management dimensions at a high level When considering each aspect, it was found that the first place was the vision creation aspect, followed by the vision dissemination aspect. And lastly, is the implementation of the vision. 2) Overall academic administration is at a high level. When considering each item, it was found that the first place was in the aspect of evaluation and comparison of the results transfer, followed by the teaching and learning management in educational institutions. in the field of curriculum development for educational institutions and the last place is the development of the learning process. 3) Vision in the administrative dimension and academic administration of Naluang School Bangkok, overall, the positive relationship was at a moderate level with a statistical significance at the 0.01 level.